2015
DOI: 10.1007/s00256-015-2227-0
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of dual-energy X-ray absorptiometry measurements of bone mineral density in the metatarsals

Abstract: Reliable measurements of BMD were achieved for the first, second and fifth metatarsals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Our assessment of bone mineral density was reliable for the 2MT and 5MT total ROI’s. These results were consistent with the findings of other research, which also found good reliability in the 2MT and 5MT [ 12 , 14 ]. In addition to the total ROI, this study found good reliability of the proximal and shaft ROI’s and poor reliability of the distal ROI.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our assessment of bone mineral density was reliable for the 2MT and 5MT total ROI’s. These results were consistent with the findings of other research, which also found good reliability in the 2MT and 5MT [ 12 , 14 ]. In addition to the total ROI, this study found good reliability of the proximal and shaft ROI’s and poor reliability of the distal ROI.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, a novel method of measuring the bone mineral density of ex-vivo metatarsals was created and found to be reliable using DXA technology. This method was adapted for the total BMD of in vivo metatarsals and found to be reliable [ 12 ]. It is uncertain how further region of interest (ROI) divisions such as proximal, shaft, and distal sections affect these results.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that some adaptation was still occurring in contractile tissue after 26 weeks of using minimalist shoes. Minimalist shoes cause a more plantar flexed ankle at initial ground contact and increase the mechanical work required by the ankle plantar flexors and it is likely that this caused the increase in strength (Firminger & Edwards, 2016; Fuller et al., 2016; Goss et al., 2015). Previous research demonstrated that 12 weeks of running in minimalist shoes increased intrinsic foot muscle cross‐sectional area (Miller, Whitcome, Lieberman, Norton, & Dyer, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo, aBMD explains ~80% of the variance in metatarsal fracture force 28 . Unfortunately, in vivo studies report low precision and accuracy for measuring metatarsal aBMD, thereby limiting clinical utility 29,30 …”
Section: Factors Associated With Metatarsal Bsimentioning
confidence: 99%
“…28 Unfortunately, in vivo studies report low precision and accuracy for measuring metatarsal aBMD, thereby limiting clinical utility. 29,30 Peripheral quantitative computed tomography (pQCT) has been used to measure the second metatarsal in cadaveric feet at 15% and 50% of the length with good precision (CV; 2.4% to 5.6% for distal site; 0.1% to 2.4% for mid-shaft). 31 However, no data are available in living individuals.…”
Section: Bone Strengthmentioning
confidence: 99%